Аналіз методів сортування в автоматичних системах виробництва - Кондратюк, М. В. (My University, 2020)
In connection with the stable height of consumer needs of enterprise force to promote the productivity. Thus they run into the row of problems, among that it is necessary to name and worsening of sorting speed, and expenses on optimization, and also increasing consumption of human resource. The systems of the computer-aided manufacturing allow to decide these difficulties.Computer-aided manufacturing it is a process at that the functions of control and management before executed by a man are fully passed to the automatic devices. For the acceleration of works apply the methods of sorting of products, for that what to manage to distribute the degree of task, execute selections from products for the exception of marriage and to implementation of different tasks.
Keywords: автоматичні системи виробництва; оптико-механічне сортування; гідравлічне сортування; повітряне сортування